Amazon Fire phone the missing manual - Gralla, Preston (The missing manual, 2014)
Unleash the powers of the Amazon Fire phone with help from technology guru Preston Gralla. Through clear instructions and savvy advice, this fast-paced, engaging guide shows you how to make the most of Fire phones innovative featuresincluding Firefly, Dynamic Perspective, one-handed gestures, and integration with Amazon Prime. The important stuff you need to know:Gain control with Dynamic Perspective. Tilt your phone to scroll, move your head to play games, and explore maps in 3D. Take pictures further. Capture high-res, panoramic, and moving (lenticular) photos. Shoot HD video, too. Shop with ease. Use Firefly to identify music, videos, and other items, and go straight to the products Amazon page. Get the apps you want. Load up on games and apps for productivity, health and fitness, and social networking from Amazons Appstore. Solve problems right away. Get live tech support from Amazon via video chat with the Mayday help feature. Carry the Cloud in your hand. Access Prime Instant Video, your Kindle library, and your uploaded photos and videos.